2018
DOI: 10.1007/s10461-018-2173-7
|View full text |Cite
|
Sign up to set email alerts
|

Does Economic Strengthening Improve Viral Suppression Among Adolescents Living with HIV? Results From a Cluster Randomized Trial in Uganda

Abstract: To assess the effect of a savings-led economic empowerment intervention on viral suppression among adolescents living with HIV. Using data from Suubi + Adherence, a longitudinal, cluster randomized trial in southern Uganda (2012–2017), we examine the effect of the intervention on HIV RNA viral load, dichotomized between undetectable (< 40 copies/ml) and detectable (≥ 40 copies/ml). Cluster-adjusted comparisons of means and proportions were used to descriptively analyze changes in viral load between study arms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 39 publications
(45 reference statements)
6
92
0
Order By: Relevance
“…The study comparing participant savings accounts to standard care also showed no statistically significant difference in viral If a study included children and/or adults, we report the total number of adolescents and youth included, the age group specified, and results specific to this age group suppression between arms. The proportion of participants with a VL < 40 copies/µl at 24 months did not significantly differ by arm − 65.9% in the intervention arm and 63.4% in the control arm [52]. The observational study of intensive adherence counseling also observed low rates of VL suppression post-counseling.…”
Section: Intervention Effectivenessmentioning
confidence: 83%
See 2 more Smart Citations
“…The study comparing participant savings accounts to standard care also showed no statistically significant difference in viral If a study included children and/or adults, we report the total number of adolescents and youth included, the age group specified, and results specific to this age group suppression between arms. The proportion of participants with a VL < 40 copies/µl at 24 months did not significantly differ by arm − 65.9% in the intervention arm and 63.4% in the control arm [52]. The observational study of intensive adherence counseling also observed low rates of VL suppression post-counseling.…”
Section: Intervention Effectivenessmentioning
confidence: 83%
“…The second study evaluated an economic intervention in which a savings account was established which could be used for small business development or education, i.e. school fees or lunches to address financial-related barriers to ART adherence [52]. In the third study, three consecutive monthly individual intensive adherence counseling sessions were provided to participants.…”
Section: Intervention Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…There was some evidence of an intervention effect on the primary outcome at midline (adjusted PR 0 [26][27].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, HIV positive patients tend to sacrifice healthcare, including adherence to treatment, and other basic needs, including food and school fees for children due to financial constraints [15][16][17][18]. Despite the limited literature on economic empowerment (EE) and adolescent adherence, existing research suggests that EE has the potential to significantly improve adherence outcomes, particularly viral suppression [15,16,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%